2000
DOI: 10.1128/aac.44.10.2903-2904.2000
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Praziquantel Increases with Concomitant Administration of Food

Abstract: In the present study we found that after a single oral dose of 1,800 mg of praziquantel, following a high-lipid diet and a high-carbohydrate diet, the maximum levels in plasma increased 243 and 515% and the area under the plasma concentration curve from 0 to 8 h increased 180 and 271%, respectively.Nine healthy volunteers participated in the study. The mean age was 33.44 years (range, 26 to 47 years), and the mean weight was 72.22 Ϯ 11.29 kg. The protocol was approved by the local ethics committee, and informe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 10 publications
2
56
1
5
Order By: Relevance
“…When comparing our data with those obtained in previous studies, we found that the influence of grapefruit juice on the AUC of praziquantel is comparable to that observed with cimetidine and lower than that observed with food (1.65-and 2.7-fold for AUC, respectively) (6,12).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…When comparing our data with those obtained in previous studies, we found that the influence of grapefruit juice on the AUC of praziquantel is comparable to that observed with cimetidine and lower than that observed with food (1.65-and 2.7-fold for AUC, respectively) (6,12).…”
supporting
confidence: 55%
“…The specific cytochrome P450 enzymes involved in the metabolism of praziquantel in humans have not been characterized (5), but a significant inhibition of praziquantel hydroxylation by compounds that are inhibitors for 3A isoforms of cytochrome P450 has been observed in microsomes isolated from rat liver (16). In previous studies in humans, it was shown that cimetidine (an inhibitor of the microsomal cytochrome P450 mixed-function oxidase system) or simultaneous food administration increased the levels in plasma of praziquantel (6,12); therefore, the aim of this study was to investigate the effect of the ingestion of grapefruit juice on the pharmacokinetics of praziquantel.…”
mentioning
confidence: 99%
“…Dexamethasone decreases plasma concentration of PZQ but increases ASOX [26,37]. Food, a high carbohydrate diet, grapefruit juice and cimetidine increase plasma PZQ concentration [26,30,[56][57][58]. Foods rich in fat and cimetidine may also favor ALB absorption.…”
Section: Failure Of Anticysticercal Therapy: Possible Explanationsmentioning
confidence: 99%
“…This calls for well designed trials incorporating also pharmacokinetic assessment, possibly with sparse sampling and population kinetic assessment. These trials should also control for food intake, as the bioavailability of PZQ depends upon taking it with food and the type of food matters (Mandour et al 1990 ;Castro et al 2000). The rationale behind the widely spaced dosing intervals of metrifonate treatment derives from its long-lasting effect on red blood cells and plasma cholinesterases (Plestina, Davis and Bailey, 1972).…”
Section: Public Health Implicationsmentioning
confidence: 99%